Fattening heifers for the summer or early fall market, 1947-48. - Pickett, A.G.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
Eight lots of heifers are being used in the current test. All eight lots have been wintered on a daily ration of 20 pounds Atlas sorgo silage, full access to prairie hay in racks, and 8 protein supplement. Dehydrated brome grass and dehydrated alfalfa pellets and a combination of dehydrated brome grass and cottonseed meal were compared with the standard oil seed meals and with mustard seed meal. In addition to the above ration, lots 1 to 5 inclusive received 2 pounds ground shell corn.
Keywords: Beef; Heifers; Market; Brome grass